2007
DOI: 10.1111/j.1471-4159.2007.04972.x
|View full text |Cite
|
Sign up to set email alerts
|

Congo red and thioflavin‐T analogs detect Aβ oligomers

Abstract: Several small molecule ligands for amyloid‐β (Aβ) fibrils deposited in brain have been developed to facilitate radiological diagnosis of Alzheimer’s disease (AD). Recently, the build‐up of Aβ oligomers (AβO) in brain has been recognized as an additional hallmark of AD and may play a more significant role in early stages. Evidence suggests that quantitative assessment of AβO would provide a more accurate index of therapeutic effect of drug trials. Therefore, there is an urgent need to develop methods for effici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
172
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(180 citation statements)
references
References 51 publications
8
172
0
Order By: Relevance
“…It has been found that AβOs are highly neurotoxic and kill hippocampal neurons at nanomolar concentrations [27] . AβOs accumulate at synaptic sites [36] , where they bind to postsynaptic density complexes with a high affinity [14,37] and disrupt synaptic plasticity [38,39] . This provides strong evidence for direct AβO toxicity to post-synaptic components, a possible physical basis of synaptic dysfunction in AD.…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that AβOs are highly neurotoxic and kill hippocampal neurons at nanomolar concentrations [27] . AβOs accumulate at synaptic sites [36] , where they bind to postsynaptic density complexes with a high affinity [14,37] and disrupt synaptic plasticity [38,39] . This provides strong evidence for direct AβO toxicity to post-synaptic components, a possible physical basis of synaptic dysfunction in AD.…”
Section: Discussionmentioning
confidence: 99%
“…The SPR protocol for the study of real-time direct binding of Ab and DBP was essentially similar to that described previously 47,48 and was performed using a Biacore X-100 (GE Healthcare). The CM5 sensor chip (GE Healthcare) was preactivated by a mixture of N-hydroxysuccinimide and N-ethyl-N'-(dimethylaminopropyl) carbodiimide.…”
Section: Methodsmentioning
confidence: 99%
“…First, we assessed the areas and distribution of aggregate positives with BSB, a derivative of Congo Red that is more prone to stain oligomers than fibrils. 29 Brain sections from wild-type mice, APP-PS1 control, APP-PS1 lithium-and APP-PS1 rosiglitazone-treated mice were stained with BSB and analyzed for area fraction and plaque density (Figure 8a-f). This analysis showed a reduction in the positive area of BSB staining in the hippocampus by both treatments (Figure8h).…”
Section: Lithium and Rosiglitazone Treatment Reduces Inflammatory Reamentioning
confidence: 99%
“…24,26,27 BSB ([(trans,trans)-1-Bromo-2,5-bis-(3-hydroxycarbonyl-4-hydroxy)-styrylbenzene) staining was performed as described earlier. 28,29 Briefly, the mounted sections were dehydrated and rehydrated in graded ethanol solutions, stained with BSB solution (200 mM) in 50% ethanol for 30 min, washed with saturated solution of lithium carbonate, differentiated with 50% ethanol and covered using a fluorescentmounting medium.…”
Section: Immunohistochemical Proceduresmentioning
confidence: 99%